Aspectos do processo de nasalização automática em uma variedade do português falado no Recife - Mendonça, Ana Maria Santos de (2015)
The nasalization is considered to be one of the phonological and phonetic features which distinguish Portuguese from several other languages; it is, therefore, considered to be one of the most important features of Portuguese language. According to Câmara Jr. (1970), the nasal vowels result from the contact between a vowel and a nasal consonant. That hypothesis is, in this study, considered as the general rule guiding the nasalization phenomenon of the vowel in Portuguese. From what we call a general rule, we can consider two types of nasalization: One is usually called contrastive or phonemic nasalization, for having distinctive function, and the other is called automatic or phonetic nasalization since it doesn´t distinguish any meaning. Based on the presumptions of autossegmental phonology, we study, in this research, the nasalization process of a variety of spoken Portuguese in Recife. We emphasize on the automatic nasalization process which occurs when a vowel assimilates the nasal feature of the nasal consonant of the following syllable, for example, in [ˈkama] (bed) and [mĩˈɲᴐka] (worm).Considering the general rule determining that a vowel is nasalized before a nasal consonant, we seek to describe that factors, in the nasalization process called up till now automatic nasalization, favor the following realization´s possibilities: (i) the vowel, even before a nasal consonant, suffers variation, in other words, it can be nasalized or not, or (ii) the vowel, even before a nasal consonant considered the trigger leading to the process of the vowel nasalization in Portuguese, is never nasalized. In order to undertake this study, we selected excerpts of interviews collected by NURC/RE Project, containing words that havea vowel followed by a nasal consonant and divided into groups. For these groups, we consider the linguistic factors that can facilitate or block nasalization rule. The selected factors were: the syllabic structure, the point of articulation of the nasal consonant and the accentual context of the vowel target of nasalization. The results show that these factors have a role in the categorization of vowel nasalization rule as well as in its optionality or blockage.